Continuous deep sedation versus minimal sedation after cardiac arrest and resuscitation (SED-CARE): A protocol for a randomized clinical trial - Ceric, A; Dankiewicz, J; Hästbacka, J; Young, P; Niemelä, V H; Bass, F; Skrifvars, M B; Hammond, N; Saxena, M; Levin, H; Lilja, G; Moseby-Knappe, M; et al. (Acta anaesthesiologica Scandinavica, 2025)
BACKGROUND: Sedation is often provided to resuscitated out-of-hospital cardiac arrest (OHCA) patients to tolerate post-cardiac arrest care, including temperature management. However, the evidence of benefit or harm from routinely administered deep sedation after cardiac arrest is limited. The aim of this trial is to investigate the effects of continuous deep sedation compared to minimal sedation on patient-important outcomes in resuscitated OHCA patients in a large clinical trial. METHODS: The SED-CARE trial is part of the 2 × 2 × 2 factorial Sedation, Temperature and Pressure after Cardiac Arrest and Resuscitation (STEPCARE) trial, a randomized international, multicentre, parallel-group, investigator-initiated, superiority trial with three simultaneous intervention arms. In the SED-CARE trial, adults with sustained return of spontaneous circulation (ROSC) who are comatose following resuscitation from OHCA will be randomized within 4 hours to continuous deep sedation (Richmond agitation and sedation scale (RASS) -4/-5) (intervention) or minimal sedation (RASS 0 to -2) (comparator), for 36 h after ROSC. The primary outcome will be all-cause mortality at 6 months after randomization. The two other components of the STEPCARE trial evaluate sedation and temperature control strategies. Apart from the STEPCARE trial interventions, all other aspects of general intensive care will be according to the local practices of the participating site. Neurological prognostication will be performed according to European Resuscitation Council and European Society of Intensive Care Medicine guidelines by a physician blinded to the allocation group. To detect an absolute risk reduction of 5.6% with an alpha of 0.05, 90% power, 3500 participants will be enrolled. The secondary outcomes will be the proportion of participants with poor functional outcomes 6 months after randomization, serious adverse events in the intensive care unit, and patient-reported overall health status 6 months after randomization. CONCLUSION: The SED-CARE trial will investigate if continuous deep sedation (RASS -4/-5) for 36 h confers a mortality benefit compared to minimal sedation (RASS 0 to -2) after cardiac arrest.
Keywords: cardiac arrest; zástava srdce mimo nemocnici; Out-of-Hospital Cardiac Arrest; Adult; dospělí; Humans; randomized clinical trial; Conscious Sedation; lidé; hluboká sedace; kardiopulmonální resuscitace; Randomized Controlled Trials as Topic; Cardiopulmonary Resuscitation; Deep Sedation; sedation; randomizované kontrolované studie jako téma; analgosedace